Enhancing mild steel surface characteristics through electrical discharge coating with titanium dioxide suspension - Liew, Pay Jun; Mustapa Kamil, Nurnabihah Najaa; Othman, Intan Sharhida; Salleh, Mohd Shukor; Wang, Jingsi (Penerbit Akademia Baru, 2024)
In this research, surface modification of mild steel was carried out by using electric discharge coating (EDC) with titanium dioxide (TiO2) powder suspension. The concentrations of TiO2 powder were varied and their effect on the surface roughness and deposited element were investigated. The results showed that elements such as titanium, carbon, copper, oxygen, zinc and iron were successfully coated on the mild steel surface. Aside from that, the weight % of the titanium element increased with an increase of TiO2 powder concentration. The surface roughness was also reduced 62.9% by using 5 g/l TiO2 powder when compared to the pure kerosene oil.